2001
DOI: 10.1080/00288330.2001.9516997
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of drift‐dive estimates of brown trout (Salmo trutta) abundance in two New Zealand rivers: A mark‐resighting study

Abstract: We compared raw drift-dive counts of adult brown trout (Salmo trutta Linnaeus 1758) with population estimates calculated from mark-resight techniques on two occasions in two back-country rivers near Nelson, New Zealand. Trout were caught by angling and marked with colour-coded dart tags between 1 and 7 days before drift dives were carried out. Drift-dive counts in the Owen and Ugly Rivers were 57-66% and 21-43%, respectively, of the population estimates calculated using the markresight techniques. Although und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 17 publications
0
24
1
Order By: Relevance
“…More recently, observer efficiency estimates for diver counts of westslope cutthroat trout in the Wigwam and Bull rivers in southeastern British Columbia were 79% at 12.9-m average horizontal visibility and 81% at 12.2-m visibility, respectively (unpublished data). Diver counts of nonnative brown trout Salmo trutta were between 57% and 66% of the mark-recapture estimates at approximately 7-m horizontal visibility in one of two New Zealand rivers studied by Young and Hayes (2001), and 21-43% in the other at approximately 10-m visibility. The lower levels of accuracy were found in the system with more instream cover despite a better level of visibility.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…More recently, observer efficiency estimates for diver counts of westslope cutthroat trout in the Wigwam and Bull rivers in southeastern British Columbia were 79% at 12.9-m average horizontal visibility and 81% at 12.2-m visibility, respectively (unpublished data). Diver counts of nonnative brown trout Salmo trutta were between 57% and 66% of the mark-recapture estimates at approximately 7-m horizontal visibility in one of two New Zealand rivers studied by Young and Hayes (2001), and 21-43% in the other at approximately 10-m visibility. The lower levels of accuracy were found in the system with more instream cover despite a better level of visibility.…”
Section: Discussionmentioning
confidence: 90%
“…Such behavior could affect counting accuracy in lower visibility conditions, or when the line of divers has been broken up in complex currents. Young and Hayes (2001) suggested that brown trout in New Zealand rivers reacted to divers by moving into cover when it was available, behavior which appeared to have a significant effect on observer efficiency. In contrast, Schill and Griffith (1984) and Zubik and Fraley (1988) both indicated that westslope cutthroat trout showed little reaction to the presence of divers, observations that appear to be true for the subspecies in southeastern British Columbia rivers as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature S. salar were identified with respect to species and sex and classified into one of three size groups largely corresponding to age at sea. Due to methodological constraints including underwater visibility and avoidance behaviour of S. salar, the count surveys probably underestimated the actual size of spawning stocks (Young & Hayes, 2001;Orell & Erkinaro, 2007). In a tributary of the large sub-Arctic Teno River in northern Scandinavia (underwater visibility 11-12 m, width 3-30 m, depth <2·5 m) Orell et al (2011) estimated the observation efficiency to be 81-82% of the true population of adult of S. salar.…”
Section: A D U Lt S S a L A R R E T U R N T O T H E R I V E Rmentioning
confidence: 99%
“…Visual methods for estimating trout abundance are appealing in clear-water rivers because they are relatively simple to conduct, inexpensive, and noninvasive. Underwater surveys by snorkel divers are commonly undertaken in North America and elsewhere, when visibility permits (e.g., Young and Hayes 2001;Joyce and Hubert 2003;Hagen and Baxter 2005;Orell and Erkinaro 2007). In New Zealand, drift diving is the preferred method for assessing abundance of adult resident trout populations in clear-water rivers and has been well tested (Hicks and Watson 1985;Teirney and Jowett 1990;Richardson 1992;Young and Hayes 2001).…”
mentioning
confidence: 99%